Automated Issue Prediction in Vehicle Development: Leveraging AI for Operational Excellence - Sree Ramya Yendluri (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the transformative impact of automated issue prediction systems in modern vehicle development, focusing on the integration of artificial intelligence and machine learning technologies. This article examines how these advanced systems revolutionize traditional diagnostic approaches by implementing predictive maintenance strategies and real-time monitoring capabilities. Through comprehensive analysis of data utilization, machine learning models, and real-time implementation frameworks, the article demonstrates how automated systems enhance vehicle reliability and operational efficiency. This article investigates the implementation challenges and solutions, highlighting the importance of robust data integration, model validation protocols, and system integration methodologies. This article presents a detailed case study showcasing the practical application of these technologies in automotive manufacturing environments, emphasizing the significant improvements in maintenance processes, resource optimization, and engineering efficiency. By examining various aspects of automated issue prediction, from theoretical foundations to practical implementations, this article provides valuable insights into the future of automotive development and maintenance strategies.